Pray as you have see me pray [videorecording] - Al Shaik, Subhi; One Islam Production; Saba Islamic Media ([Australia] : One Islam Production ; Kuala Lumpur : Saba Islamic Media (distributor), 2004)
This includes the night journey of the Prophet Muhammad (pbuh) which called Isra' Mi'raj, the hygiene (Taharah), abulation (wudu, tayammum), prayer and also the benefits of prayer and abulation. This program more focus on learn to pray the way The Prophet Muhammad (pbuh) prayed
Title from title screen
Narration: Barry Sadlier
Keywords: Prayer -- Islam; Islam